Sintilimab as maintenance treatment for local/regional recurrent esophageal squamous carcinoma after concurrent chemoradiotherapy: a single-arm Ib/II phase study - Liu, Chengxin; Sun, Hongfu; Huang, Wei; Wang, Zhongtang; Fu, Chengrui; Han, Dan; Zhao, Qian; Wu, Xue; Li, Baosheng (Frontiers in Immunology, 2023)
Background Esophageal cancer (EC) is an aggressive neoplasm of the gastrointestinal tract that is usually treated with a combination of chemotherapy, radiotherapy (RT), and/or surgery, according to disease status. Despite the availability of multimodal therapeutic strategies, local recurrence is frequently observed. However, there is no standard treatment or promising therapeutic approach for local recurrence or metastatic esophageal carcinoma after the RT. This study tended to investigate the efficacy and safety of sintilimab maintenance after concurrent chemoradiotherapy (CCRT) for local/regional recurrent esophageal squamous carcinoma. Methods This study was a single-arm, phase Ib/II trial conducted in a single site in China. Patients previously radically treated (surgery or CCRT), histologically confirmed, local or regional recurrence esophageal squamous carcinoma, qualified for the study design, were treated with 25–28 times radiotherapy plus raltitrexed once every 3 weeks for up to two cycles. Patients who have not progressed after CCRT received sintilimab as maintenance once every 3 weeks up to 1 year. Primary endpoints were overall survival (OS) and safety. Secondary endpoints were progression-free survival (PFS), objective response rate (ORR), and duration of response (DOR). Results Between September 2019 and March 2022, in a total of 36 enrolled patients, 34 pts completed CCRT. Three patients excluded due to violation of the exclusion criteria (1 pt) and consent withdrawal (2 pts). Finally, 33 pts were included in the final analysis, in which 3 pts had disease progression, and the remaining 30 entered maintenance therapy with sintilimab. The median follow-up time was 12.3 months. Median OS was 20.6 months (95%CI 10.5–NA) and the 1-year OS rate was 64%. Median PFS was 11.5 months (95%CI 5.29–21.3) and the 1-year PFS rate was 43.6%. The ORR was 63.6% (95%CI 44.6–77.8), including 2 cases of CR and 19 cases of PR. The DCR was 19.9%, the median DOR was 19.5 months, and the median TTR was 2.4 months. The rate of any grade TRAEs was 96.7%; ≥Grade 3 TRAE was 23.4%. The incidence of immune-related AE was 60%, most of which were grade 1–2, and only one case of thyroid-stimulating hormone increased was irAE with grade 3 or above. Conclusion Sintilimab has shown promising clinical efficacy and a manageable safety profile as maintenance therapy after CCRT for local/regional recurrent esophageal squamous carcinoma. In addition, further confirmation from a large-scale real-world study is still needed.